Intelligent humanoid emotion response based on human emotion recognition for virtual intercommunication simulator - Wei Chin, Andrew Lim; Wen, Lim Gim; Syafiq Fauzi, Kamarulzaman (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper aims to introduce a computational emotion model, named Fuzzy Artificial Intelligence Human Emotion Response (FATHER) after reviewing recent research on human emotion responses in human-machine interactions. Emotions play a pivotal role in human communication, influencing our moods and responses. The research delves into fundamental human emotions, computational emotion models, face detection algorithms, and fuzzy logic inference systems. FATHER is proposed and integrated into a 3D humanoid character named Umar. Umar's responses are presented using a virtual 3D human face model, allowing emotion expression through facial animations. This integration of 3D modeling and animation not only reduces costs linked with physical robotics but also propels advancements in affective computing research.